Juggling investigation and interpretation: The problematic dual role of police officer-interpreter - Filipovic, Luna; Vergara, Suzanne Abad (Language and Law / Linguagem e Direito, 2018)
This article is a case study example of problems that arise when a bilingual police officer interrogates a suspect and acts as interpreter at the same time, thus creating a conflict of interest that is diffcult to resolve. We shed light on the challenges that both officers and suspects face in multilingual communication when professional interpretation is not available. Our focus is on both language inaccuracies due to language incompetence and communication problems due to lack of impartiality because of the offiicer-interpreter’s primary commitment to investigation rather than unbiased interpretation. We explain why assuming the two roles, interrogator and interpreter, creates numerous diculties: linguistic, ethical and, potentially, legal. We also illustrate how the constant switching between the two roles exerts intense cognitive pressure on the officer, which professional interpreters are trained to deal with, but the officer-interpreter is not. The consequence is an enhanced negative impact on accuracy and efficiency in evidence elicitation.